Inpatient Treatment of People With Schizophrenia: Quantifying Clinical Change Using the Health of the Nation Outcome Scales. Issue 1 (6th July 2021) - Lay, Barbara; Roser, Patrik; Kawohl, Wolfram
Abstract: Schizophrenia can require hospital inpatient care in crisis periods or times of severe symptoms, although the length of hospital stays has been considerably reduced in the last few decades. Evidence on individual outcomes under routine psychiatric practice conditions is sparse. This study aims to evaluate the outcomes of inpatient treatment in patients with schizophrenia using the reliable and clinically significant change approach. We used routinely collected Health of the Nation Outcome Scales (HoNOS) data to assess the extent to which and the areas where symptomatic and functional improvement was achieved. Data from 1783 schizophrenia patients admitted to a large psychiatric centre in Switzerland were examined. Mean HoNOS total score dropped from 17.9 to 11.7 (effect size 0.8) during treatment; the greatest improvements were achieved regarding symptomatic problems and aggressive, agitated behavior. According to the reliable change index formula, 24.5% of patients were to be considered improved, 73.3% unchanged and 2.2% deteriorated. In total, 56.6% were discharged from the hospital in a subclinical or mild functional state. The degree of individual improvement and time to achieve maximum symptom reduction varied considerably, depending on the patients' functional state at admission, as did the length of hospital stay (median 28 days). Rates of readmission within 28 days (17.8%) were significantly lower in patients with clinically significant improvement, discharged in better clinical condition. These findings support reconsidering (length of) inpatient treatment within the overall framework of meaningful clinical change and subsequent treatment needs in patients with schizophrenia.